Pengaruh Pertumbuhan Ekonomi, Upah Minimum Serta Tingkat Pendidikan Terhadap Penyerapan Tenaga Kerja Di Provinsi Sumatera Utara Tahun 2010 – 2020 - Rozaini, Noni; Sulfina, Sri Dai (CV. ITTC INDONESIA, 2022)
The demand for labor is closely related to the quantity of labor needed to fill jobs in a company or other agency. Analysis of labor demand is based on the assumption that labor market demand is derived from public demand for the goods and services they need. Labor demand is the relationship between wage rates, labor supply is a function of wages. in this research is to examine economic growth, minimum wages, level of education on employment in North Sumatra Province in 2010 - 2020. This research is a study that uses a quantitative approach method. A quantitative approach is carried out by looking at the extent to which economic growth, education level, and minimum wages influence the absorption of labor in North Sumatra Province. The purpose of this research is to find out and analyze how the influence of economic growth, minimum wages and education level on employment in North Sumatra Province in 2010 - 2020. This research uses secondary data originating from the Central Bureau of Statistics for North Sumatra Province in 2010 - 2020. And the data analysis method used in this research is multiple linear regression analysis using eviews 12.